2019
DOI: 10.1038/s41467-019-08880-0
|View full text |Cite
|
Sign up to set email alerts
|

Tightly-orchestrated rearrangements govern catalytic center assembly of the ribosome

Abstract: The catalytic activity of the ribosome is mediated by RNA, yet proteins are essential for the function of the peptidyl transferase center (PTC). In eukaryotes, final assembly of the PTC occurs in the cytoplasm by insertion of the ribosomal protein Rpl10 (uL16). We determine structures of six intermediates in late nuclear and cytoplasmic maturation of the large subunit that reveal a tightly-choreographed sequence of protein and RNA rearrangements controlling the insertion of Rpl10. We also determine the structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 66 publications
2
84
0
Order By: Relevance
“…The maps allowed us to fit and refine atomic models for all six assembly states, including the biogenesis factors Arx1, Lsg1, Nmd3, Rei1, Reh1, eIF6, ribosomal proteins eL40, uL16 and uL11 together with the 5S, 5.8S and 25S rRNA (Figure 1B, Figure 1—figure supplements 2–4, Supplementary file 1A, B). In addition, we identified density corresponding to the phosphatase (Baßler et al, 2017) and zinc finger (Zhou et al, 2019) domains of Yvh1 situated between uL11 in the P-stalk and eIF6 (Figure 1A, states I-II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maps allowed us to fit and refine atomic models for all six assembly states, including the biogenesis factors Arx1, Lsg1, Nmd3, Rei1, Reh1, eIF6, ribosomal proteins eL40, uL16 and uL11 together with the 5S, 5.8S and 25S rRNA (Figure 1B, Figure 1—figure supplements 2–4, Supplementary file 1A, B). In addition, we identified density corresponding to the phosphatase (Baßler et al, 2017) and zinc finger (Zhou et al, 2019) domains of Yvh1 situated between uL11 in the P-stalk and eIF6 (Figure 1A, states I-II).…”
Section: Resultsmentioning
confidence: 99%
“…Our study suggests that Yvh1 dissociates from the pre-60S particle prior to the binding of eL40 and uL16 (Figure 1A). However, while this work was under review, Yvh1 was reported to bind cytoplasmic pre-60S particles carrying eL40 and uL16 (Zhou et al, 2019). Perhaps explaining this discrepancy, our study has exclusively analysed native pre-60S particles, while Zhou et al examined particles purified from Rlp24-mutant cells or following treatment with the inhibitor diazaborine (Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in cryogenic-electron microscopy (cryo-EM) have shed a tremendous amount of light on the process of RP nuclear import and their incorporation into the ribosome. For further information on this aspect of ribosome biogenesis, the reader is encouraged to see the following publications: [12,14,15,16,17,18,19] (Figure 1).…”
Section: Ribosome Biogenesis: An Overviewmentioning
confidence: 99%
“…From the early nucleolar stage onwards, distinct maturation intermediates (pre-ribosomal particles) are characterized and classified by their association with specific maturation factors. Pioneering work from several laboratories has unveiled structural snapshots of several of these pre-60S precursor particles from yeast (Figure 2) [27,28,29,30,31,32,33,34,35,36,37]. Defining the structure and composition of these particles has uncovered the metamorphosis of the large ribosomal subunit during maturation; however, many gaps still remain in the blueprints of ribosome assembly (recently reviewed in [3,4,5,6]).…”
Section: Aaa-atpases In Ribosome Biogenesismentioning
confidence: 99%